PENINGKATAN KETERAMPILAN MENULIS FEATURE MELALUI PENDEKATAN KONTEKSTUAL MAHASISWA SEMESTER VI PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UMSB PADANG PANJANG - Rita Arianti (JURNAL PENDIDIKAN ROKANIA, 2016)
The purpose of research is to describe: (1) Intensifying the process of features writing skills of students,(2) the result of an increase in student features writing skills in student of VI Semester Study Program Indonesian Language and LiteratureIndonesia FKIP UMSB Padang Panjang. Data was obtained from qualitativedata in the form of sheets observation, field note, questionnaires, and quantitative data in the form of test performanc. The findings of a study of the process ofimproving features writing skills through contextual teaching learning Language Study Program and Literature Indonesia FKIP UMSB Padang Panjang performing well. The average student test results has increased, averaging at 56,6pracycle, in the first cycle 65 and the second cycle 75.